2017
DOI: 10.1007/978-981-10-5122-7_209
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal activity asymmetry in sleep - a case study for migraine detection

Abstract: Migraine is a poorly understood disease and it is estimated that 15% of people in Europe alone are affected by it. In this study skin electrodermal activity (EDA) signals of left and right wrists were collected from a migraine patient to see if the asymmetry associated with EDA signals will affect to migraine detection based on wearable sensors. In the study, nighttime EDA storm epochs were detected and visual inspection on total time of EDA storm epochs and timing of EDA storms between wrists were done. Also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Sleep as a mental procedure is highly correlated to physiological signals. This fact is proven under experiments, which involve monitoring sleep stages using PSG [33][34][35][36][37]45,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Therefore, we propose a novel clinical decision support system to predict the sleep quality based on trends of physiological signals in deep sleep stage.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep as a mental procedure is highly correlated to physiological signals. This fact is proven under experiments, which involve monitoring sleep stages using PSG [33][34][35][36][37]45,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Therefore, we propose a novel clinical decision support system to predict the sleep quality based on trends of physiological signals in deep sleep stage.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…To enhance the performance and reliability of measurements, small contact-based devices (e.g. Empatica E4 wristband [15]) can be used [45]. As stated in [46][47][48], this easy-to-use device enables us to monitor important physiological signals during sleep while it does not interrupt regular sleep pattern.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also showed that most of the participants wanted the device to be located on the wrist, either in the watch, bracelet, or skin patch [23]. Sleep quality is associated with migraine birth and sleep disorder is a major trigger of migraine, also raising the body's stress hormone [26]. A study of wearable sensor to detect migraine attacks by using the Empatica E4 wristband showed that migraine attacks start at night and migraine patients wake up to headaches.…”
Section: Related Workmentioning
confidence: 99%
“…For migraine attack recognition, solutions based on sleep monitoring with Empatica E4 sensor [26][27][28] or ambulatory data [11] have also been studied.…”
Section: Wearable Sensors and Self-trackingmentioning
confidence: 99%